1993
DOI: 10.1002/cbf.290110102
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of expression of prion protein in uninfected and scrapie‐infected N2a mouse neuroblastoma cells

Abstract: The scrapie prion protein, PrPSc, is formed from its isoform, the cellular PrPc. There is evidence available indicating that PrPSc is a necessary component of the infectious prion particle to cause a series of transmissible spongiform encephalopathies. We have used immunocytochemistry and RNA blotting techniques to investigate if infection with prions results in an increased PrP gene expression. For the experiments we used N2a cells which had been infected with prions (ScN2a cells). We demonstrated by confocal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 38 publications
1
11
0
1
Order By: Relevance
“…These results were independent of the N2a cell line, because similar results were observed with Chinese hamster ovary cells overexpressing MoPrP (data not shown). Interestingly, we can also detect the presence of PrP in the nuclei of the cells, presumably in the nucleoli, as already described (18,19).…”
Section: Effect Of Rab Proteins On Endogenous Prpsupporting
confidence: 84%
“…These results were independent of the N2a cell line, because similar results were observed with Chinese hamster ovary cells overexpressing MoPrP (data not shown). Interestingly, we can also detect the presence of PrP in the nuclei of the cells, presumably in the nucleoli, as already described (18,19).…”
Section: Effect Of Rab Proteins On Endogenous Prpsupporting
confidence: 84%
“…In neuroblastoma cells, PrP-mRNAs have a half-life of approximately 7 hours (Pfeifer et al, 1993) and PrP-sen is synthesized and degraded relatively rapidly (tg ~5 hours). Whereas, PrP-res aggregates which derived from PrP-sen, is (0) or in the presence of increasing concentrations of Prnp gene-specific siRNA or of scrambled siRNA duplexes.…”
Section: Discussionmentioning
confidence: 99%
“…PrP sc is translocated into nuclei 73 where confocal laserscanning microscopy on infected neuroblastoma cells has revealed that PrP and/or PrP sc preferentially reside within nucleoli. 74 Biochemical association of ros sequences with nucleoli may therefore favor PrP interactions.…”
Section: Potential Association With the Nucleolusmentioning
confidence: 99%